Coherent Changes in Neural Motor Network Activity during Levodopa-Induced Dyskinesia in a Rat Model of Parkinson’s Disease - Elena S. Brazhnik; Ivan E. Mysin; Lyudmila B. Popova; Vladislav V. Minaychev; Nikolay I. Novikov (Journal of Integrative Neuroscience)
Background: Long-term use of levodopa, a metabolic precursor of dopamine (DA) for alleviation of motor symptoms in Parkinson’s disease (PD), can cause a serious side effect known as levodopa-induced dyskinesia (LID). With the development of LID, high-frequency gamma oscillations (~100 Hz) are registered in the motor cortex (MCx) in patients with PD and rats with experimental PD. Studying alterations in the activity within major components of motor networks during transition from levodopa-off state to dyskinesia can provide useful information about their contribution to the development of abnormal gamma oscillations and LID. Methods: Freely moving rats with unilateral 6-hydroxydopamine hydrobromide (6-OHDA)-induced nigral DA cell lesions were administered a high dose of levodopa for 7 days. Local field potentials (LFPs) and neuronal activity were recorded from electrodes implanted in the motor cortex (MCx), ventromedial nucleus of the thalamus (VM), and substantia nigra pars reticulata nucleus (SNpr). Results: Levodopa reduced the power of beta oscillations (30–36 Hz) associated with bradykinesia in PD rats in three divisions of the motor neural network (MCx, VM, and SNpr) and prompted subsequent emergence of robust high-frequency gamma oscillations (80–120 Hz) in VM and MCx, but not SNpr, LFPs. Gamma oscillations were strongly associated with the occurrence of abnormal involuntary movements (AIMs) and accompanied by an increase in spiking rates in the VM and MCx and enlarged spike-LFP synchronization with cortical gamma oscillations (68% in the VM and 34% in the MCx). In contrast, SNpr LFPs did not exhibit gamma oscillations during LID, and neuronal activity in most recordings (87%) was largely decreased and not synchronized with VM or MCx LFPs. Administration of the antidyskinetic drug 8-hydroxy-2-(dipropylamino)-tetraline hydrobromide (8-OH-DPAT) restored the initial characteristics of LFPs (30–36 Hz oscillations), rates of neuronal activity, and bradykinesia. Inhibition of VM neurons by the gamma-aminobutyric acid (GABA-A)-agonist muscimol during LID eliminated high gamma oscillations in the MCx and VM, but not dyskinesia, suggesting that gamma oscillations are not critical for the expression of AIMs. In contrast, chemogenetic activation of SNpr neurons during LID eliminated both gamma oscillations and dyskinesia. Conclusions: These findings suggest that levodopa treatment leads to crucial reduction of inhibitory control over motor networks due to a large decline in spiking of most SNpr GABAergic projecting neurons, which causes persistent hyperactivity in motor circuits, leading to the appearance of thalamocortical gamma oscillations and LID.